Genetic association of hypertension and several other metabolic disorders with Bell’s palsy - Liu, Huawei; Sun, Qingyan; Bi, Wenting; Mu, Xiaodan; Li, Yongfeng; Hu, Min (Frontiers in Genetics, 2023)
Background Effects of hypertension, type 2 diabetes and obesity on Bell's palsy risk remains unclear. The aim of the study was to explore whether hypertension and these metabolic disorders promoted Bell's palsy at the genetic level. Methods Genetic variants from genome-wide association studies for hypertension, type 2 diabetes, body mass index and several lipid metabolites were adopted as instrumental variables. Two-sample Mendelian randomization including IVW and MR-Egger was used to measure the genetic relationship between the exposures and Bell's palsy. Sensitivity analyses (i.e. Cochran’s Q test, MR-Egger intercept test, “leave-one-SNP-out” analysis and funnel plot) were carried out to assess heterogeneity and horizontal pleiotropy. All statistical analyses were performed using R software. Results Hypertension was significantly associated with the increased risk of Bell's palsy (IVW: OR = 2.291, 95%CI = 1.025 ~ 5.122, P = 0.043; MR-Egger: OR = 16.445, 95%CI = 1.377 ~ 196.414, P = 0.029). Increased level of LDL cholesterol might upexpectedly decrease the risk of the disease (IVW: OR = 0.805, 95%CI = 0.649 ~ 0.998, P = 0.048; MR-Egger: OR = 0.784, 95%CI = 0.573 ~ 1.074, P = 0.132). In addition, type 2 diabetes, body mass index and other lipid metabolites were not related to the risk of Bell's palsy. No heterogeneity and horizontal pleiotropy had been found. Conclusion Hypertension might be a risk factor for Bell's palsy at the genetic level, and LDL cholesterol might reduce the risk of the disease. These findings (especially for LDL cholesterol) need to be validated by further studies.